2015
DOI: 10.3390/beverages1020095
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for the Production of Probiotic Fruit Juices

Abstract: Fruit juices represent a promising carrier for probiotic bacteria; however, there are some drawbacks and limits that could preclude their production at the industrial level, namely the survival of probiotics throughout storage, and the possible impact of bacteria on the sensory traits and overall acceptance. This review addresses the inoculation of probiotics in juices; with a special focus on the possibilities and challenges for future; i.e., why probiotics in juices and which kind of microorganisms; some dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
107
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(134 citation statements)
references
References 25 publications
1
107
0
15
Order By: Relevance
“…Fruit juices are considered candidate matrices for the incorporation of probiotics as they are ideal for consumers who are interested in low‐cholesterol foods, suffer from lactose intolerance, and / or are vegetarian . A challenge for the development of probiotic juices is the survival of the probiotic strains during the storage of the product . The low pH and the presence of phenolics have been cited as the primary factors associated with the low survival of probiotics in fruit juices .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruit juices are considered candidate matrices for the incorporation of probiotics as they are ideal for consumers who are interested in low‐cholesterol foods, suffer from lactose intolerance, and / or are vegetarian . A challenge for the development of probiotic juices is the survival of the probiotic strains during the storage of the product . The low pH and the presence of phenolics have been cited as the primary factors associated with the low survival of probiotics in fruit juices .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A challenge for the development of probiotic juices is the survival of the probiotic strains during the storage of the product. 3 The low pH and the presence of phenolics have been cited as the primary factors associated with the low survival of probiotics in fruit juices. 4 However, previous studies have reported that survival of probiotic strains in fruit juices may be enhanced by naturally occurring juice constituents (e.g., fibers, minerals, and vitamins), [5][6][7] as well as by microencapsulation techniques that protect the probiotics from adverse conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A similar trend was observed in alginate beads, although the reduction of cell count was significantly higher compared to pectin beads, both in oat (a decrease of 3.76 log) and in oat with peach-filling beverage (a decrease of 4.70 log). e pH of all the beverages was similar (4.22-4.07) (Table 5), so it can be stated that factors other than acidity influenced the viability of bacteria, such as the phenolic compounds present in fruit [2,37].…”
Section: Journal Of Food Qualitymentioning
confidence: 96%
“…Even in fermented milk products, which provide the best protection for bacteria because of their buffer properties, the survival of bacteria still remains a challenge for the industry, requiring new technological solutions [2,39]. Hansen et al [40] studied the viability of two bifidobacteria strains during storage in milk with a 2% fat content.…”
Section: Journal Of Food Qualitymentioning
confidence: 99%
See 1 more Smart Citation